Assessing of evapotranspiration models using limited climatic data in Southeast Anatolian Project Region of Turkey - Aydin, Yusuf (PeerJ (San Francisco, CA), 2021)
Evapotranspiration carries vital importance in areas with arid and semi-arid climate properties for many issues, including the planning of irrigation water as a scarce resource, the establishment of irrigation programs and conducting project design for drainage. The empirical equations used for determining plant water consumption are classified subject to the diversity of the utilized data. The Penman–Monteith method used frequently in many parts of the world as a standard method needs more climate data. Models that yield results that are similar to those of the standard method with less climate parameters are preferred due to their ease of use and wide impact. Temperature, relative humidity and radiation data for the years 2008–2017 were utilized to analyze the usability of the Hargreaves–Samani and Turc-1961 equations with regard to the estimation of reference evapotranspiration in four provinces located in Southeastern Anatolia Region. Results obtained via models were compared in pairs by way of the standard method in order to define the performance of the models. While the best performances were obtained from the comparison with the standard method and Hargreaves–Samani value pair, the comparison of the standard model with Turc displayed the lowest performance. Based on the study data, ET o-Turc values were higher in the provinces analyzed, thus displaying a lower performance. While maximum long term annual monthly average ET o-HS value was identified as 7.6 mm at Diyarbakır in July, whereas the lowest value was determined at Kilis with 5.8 mm; the highest and lowest ET o-Turc values were obtained in the same month at Diyarbakır and Kilis with 13.3 and 10.3 mm respectively. It was calculated based on the long term average annual total ET o values that while highest ET o-HS was calculated at Diyarbakır with 1,500 mm, whereas the lowest value was calculated at Batman with 1,183 mm. The highest value for ET o-Turc was obtained at Diyarbakır with 2,365 mm while Mardin had the lowest ET o value with 1,920 mm. Accordingly, based on the ET o values calculated at both cities studies based on both models, Diyarbakır had the highest values, whereas Kilis had the lowest ET o values. According to the standard method known as PM, lowest daily ET o values were calculated in all provinces, which displayed the highest performance among the models. As a result of this study, it is possible to use the Hargreaves-Samani model instead of the standard model in the absence of reliable climatic data.